INTELLIGENCE DIMENSIONS ON EMPLOYEE PERFORMANCE - Samson Laurens (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to analyze the influence of emotional intelligence, intellectual intelligence and social intelligence on the performance of employees of the Bureau of Public Relations and Protocol Regional Secretariat of Maluku Province. This study used an approach. The research approach used was quantitative, associative, survey and cross section. The population used in this study were all employees of the Bureau of Public Relations and Protocol of the Regional Secretariat of Maluku Province, consisting of 32 people. The sample is full sampling. Data were analyzed using multiple linear regression with the help of SPSS 25.00. The results of the study concluded that (1) Emotional intelligence has a positive and significant effect on the performance of the Public Relations and Protocol Bureau of the Regional Secretariat of Maluku Province; (2) Intellectual intelligence has a positive and significant effect on the performance of the Public Relations and Protocol Bureau of the Regional Secretariat of Maluku Province; (3) Social intelligence has a positive and significant effect on the performance of the Public Relations and Protocol Bureau of the Regional Secretariat of Maluku Province